Studies in doctrine - McGrath, Alister Edgar, 1953- (Grand Rapids, MI Zondervan, 1997)
Includes bibliographical references.
A compilation of the author's previously four, published, separate works: Understanding doctrine (which see also), Understanding Jesus, Understanding the Trinity(which see also), and Justification by faith (which see also).
Keywords: Theology, doctrinal; Jesus Christ -- person and offices; Trinity (Christian theology).; Justification (Christian theology).